Achieving highly efficient and stable MAPbI3 planar solar cell by embedding Cs+, Fe2+, and Cd2+ metal inorganic cations in perovskite structure. (February 2023) - Ebadi, Mohammad; Yardani Sefidi, Pariya; Samadifar, Ahmad; Salari, Dariush; Hosseini, Mir Ghasem
Abstract: Perovskite solar cells (PSCs) have been attracted the attention of many researchers due to their high conversion efficiency, low manufacturing cost, easy manufacturing steps, high light absorption, and the possibility of changing the photo electronic properties by modifying the chemical structure. Despite the mentioned advantages, the low stability of PSCs and toxicity of lead in the perovskite layer were the challenging issues in this field. In this regard, the use of mixed cation and mixed halide perovskite compounds with high crystal quality, efficiency, and stability has attracted enormous attention. In this project, Fe 2+, Cd 2+, and Cs + cations with various contents (Fe 2+  + Cd 2+ : 5% and 10%; Cs + : 5% and 10%) were partially replaced the Pb 2+ and CH3 NH3 + cations, respectively in the MAPbI3 perovskite structure through a two-step process using spin-coating. The as-synthesized [Csy MA1-y Pb1-a-b Fea Cdb I3-2a Cl2a ], (a+b): 5, 10%, y: 5, 10%) perovskites were characterized with X-ray diffraction (XRD), grazing incidence X-ray diffraction (GIXRD), and field emission scanning electron microscopy (FESEM). The optical properties of prepared compounds were investigated by ultraviolet–visible (UV–Vis) and photoluminescence (PL) spectroscopy. The photovoltaic behavior as well as stability of solar cells containing MAPbI3, [Csy MA1-y Pb1-a-b Fea Cdb I3-2a Cl2a ], (a+b): 5%, y: 5%), and [Csy MA1-y Pb1-a-b Fea Cdb I3-2a Cl2a ], (a+b): 10%, y: 10%) perovskites as active layers were evaluated by current density-voltage (I–V) under AM1.5G illumination. Results showed that partial substitution of CH3 NH3 + cations with Cs + and Pb 2+ cations with Fe 2+  + Cd 2+ in the CH3 NH3 PbI3 structure improved crystallinity and photovoltaic parameters. The average power conversion efficiency (PCE) of six solar cell containing [Csy MA1-y Pb1-a-b Fea Cdb I3-2a Cl2a ], (a+b): 10%, y: 10%) perovskite layer was 21.04% which was 1.03 and 1.21 times higher than that cells containing [Csy MA1-y Pb1-a-b Fea Cdb I3-2a Cl2a ], (a+b): 5%, y: 5%) and MAPbI3, respectively. The electrochemical impedance spectroscopy (EIS) was utilized to study the charge transfer resistance (Rct ) and recombination resistance (Rrec ) of prepared solar cells. The Rct and Rrec values of fabricated solar cell were decreased and increased, respectively in the presence of Fe 2+, Cd 2+, and Cs + inorganic cations. As a result, the [Csy MA1-y Pb1-a-b Fea Cdb I3-2a Cl2a ] perovskites can be considered as the appropriate candidate with high efficiency, stability, and low lead content in the planar perovskite solar cells. Graphical abstract: Image 1 Highlights: Fe 2+  + Cd 2+ and Cs + cations were partially replaced Pb 2+ and MA + in MAPbI3 structure, respectively. Maximum PCE of 21.11% is obtained in cell containing [Csy MA1-y Pb1-a-b Fea Cdb I3-2a Cl2a ], (a+b): 10%, y: 10%) perovskite layer. Stability of MAPbI3 -based cell improved in the presence of Fe 2+, Cd 2+, and Cs + inorganic cations.